A look beyond dietary (poly)phenols: The low molecular weight phenolic metabolites and their concentrations in human circulation. Issue 5 (29th August 2022) - Carregosa, Diogo; Pinto, Catarina; Ávila‐Gálvez, María Ángeles; Bastos, Paulo; Berry, David; Santos, Cláudia Nunes
Abstract: A large number of epidemiological studies have shown that consumption of fruits, vegetables, and beverages rich in (poly)phenols promote numerous health benefits from cardiovascular to neurological diseases. Evidence on (poly)phenols has been applied mainly to flavonoids, yet the role of phenolic acids has been largely overlooked. Such phenolics present in food combine with those resulting from gut microbiota catabolism of flavonoids and chlorogenic acids and those produced by endogenous pathways, resulting in large concentrations of low molecular weight phenolic metabolites in human circulation. Independently of the origin, in human intervention studies using diets rich in (poly)phenols, a total of 137 low molecular weight phenolic metabolites have been detected and quantified in human circulation with largely unknown biological function. In this review, we will pinpoint two main aspects of the low molecular weight phenolic metabolites: (i) the microbiota responsible for their generation, and (ii) the analysis (quali‐ and quantitative) in human circulation and their respective pharmacokinetics. In doing so, we aim to drive scientific advances regarding the ubiquitous roles of low molecular weight phenolic metabolites using physiologically relevant concentrations and under (patho)physiologically relevant conditions in humans.